2015
DOI: 10.1097/hrp.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity in Autism

Abstract: Autism Spectrum Disorder (ASD) affects 1 in 50 children between the ages of 6–17 years as per a 2012 CDC survey of parents. The etiology of ASD is not precisely known. ASD is an umbrella term, which includes low (IQ<70) to high functioning (IQ>70) individuals. A better understanding of the disorder, and how it manifests in an individual subject can lead to more effective intervention plans to fulfill the individual’s treatment needs. Magnetic resonance imaging (MRI) is a non-invasive investigational tool that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(88 citation statements)
references
References 92 publications
(157 reference statements)
8
78
1
1
Order By: Relevance
“…For further analysis, we focused on the seven fronto-parietal and temporal networks, typically involved in the executive and socio-cognitive functions, since they are proven to be relevant large-scale functional networks impaired in ASD [2,3,5,9] The seven networks, depicted in Fig. 1 , encompass the ventral stream (VENT) network, the central-executive network (EXE), the fronto-parietal left and right (respectively FPL, FPR), the auditory system (AUDI), the visual cortex (VISU) and the default-mode network (DMN).…”
Section: Resting-state Network Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…For further analysis, we focused on the seven fronto-parietal and temporal networks, typically involved in the executive and socio-cognitive functions, since they are proven to be relevant large-scale functional networks impaired in ASD [2,3,5,9] The seven networks, depicted in Fig. 1 , encompass the ventral stream (VENT) network, the central-executive network (EXE), the fronto-parietal left and right (respectively FPL, FPR), the auditory system (AUDI), the visual cortex (VISU) and the default-mode network (DMN).…”
Section: Resting-state Network Extractionmentioning
confidence: 99%
“…Over the past decade, ASD has been studied using fMRI, in setups where participants had to perform a specific task or during resting-state fMRI, in order to find a biomarker for autism. Unfortunately, current literature provides mixed and inconsistent results regarding strength and location of functional disparities [2][3][4][5] . Yet, several attempts to classify autism, based on functional connectivity measurements have been made [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Disrupted functional connectivity has been reported in autism spectrum disorder (ASD) (Vissers et al, 2012; Wass, 2011) in functional magnetic resonance imaging (fMRI) (Muller et al, 2011; Rane et al, 2015), electroencephalography (EEG) (Boutros et al, 2015; Wang et al, 2013), and magnetoencephalography (MEG) data (Lajiness-O’ Neill et al, 2014). However, the nature of these disruptions, e.g., increased or decreased connectivity and their specificity in functional domains, remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Converging findings from brain imaging research have given rise to theories on the neuroetiology of ASD. Studies on functional communication across brain networks have been reporting patterns of hypo-coherence in long-range default mode networks, inter-and intra-hemispheric hypo-connectivity, and hyperconnectivity in local and long-distance networks (Kahn et al 2015;Mohammad-Rezazadeh et al 2016;Müller et al 2011;Rane et al 2015), although the methodologies applied and results reported have been inconsistent. Moreover, the manner in which dysfunctional connectivity specifically impacts core ASD symptoms or the degree of severity has not been clearly delineated thus far.…”
Section: Introductionmentioning
confidence: 99%